Identifying the behavior change techniques used in obesity interventions: An example from the EARLY trials - Leslie A. Lytle; Heather M. Wasser; Job Godino; Pao‐Hwa Lin; Deborah F. Tate (Wiley, 2023)
Abstract Objective The dissemination of effective obesity interventions requires the documentation of key elements of the intervention. But outcome papers and other published manuscripts often lack detail that allow the replication of the intervention. The Behavior Change Technique (BCT) Taxonomy (BCTTv1) is a widely used approach to identify key elements of an intervention study. This study compares the extent to which BCTs and domains identified in studies' intervention protocol are concordant with detail from corresponding intervention design and study outcome papers. Methods Data come from four obesity interventions with complete intervention protocols as well as published intervention design and outcome papers. The number of domains and BCTs was calculated for each treatment arm and stratified by coding source. Emphasis of domains and BCTs was determined using an Analytical Hierarchy Process (AHP). Results A review of each study's intervention protocol showed the mean number of domains and BCTs used in treatment arms as 11.8 and 26.7, respectively. Primary outcome papers had a mean loss of 34% of the reported domains and 43% of BCTS as compared with intervention protocl. Design papers showed a loss of 11% and 21% of domains and BCTs, respectively. Conclusions The results confirm the limitations of using the BCTTv1 coding of outcome papers to describe obesity‐related interventions. The results also highlight the need for mechanisms that allow for a full description of intervention content such as inclusion in a supplemental section of an online journal or the use of intervention‐focused consort guidelines.